1989
DOI: 10.1029/wr025i010p02159
|View full text |Cite
|
Sign up to set email alerts
|

Density‐driven flow of gas in the unsaturated zone due to the evaporation of volatile organic compounds

Abstract: A theoretical investigation of factors affecting the gas phase transport of evaporating organic liquids in the unsaturated zone is presented. Estimates of density-dfiven advective gas flow using a simple analytic expression indicate that significant advective gas flow will result from the evaporation of volatile liquids in soils having a high permeability. Numerical simulations using a two-dimensional cylindrical geometry and including the effects of phase partitioning between the solid, gas, water, and organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(130 citation statements)
references
References 26 publications
(14 reference statements)
0
126
0
4
Order By: Relevance
“…This relationship was derived by a number of researchers using related approaches (Bear 1972;Turner 1973;Cheng and Minkowycz 1977;Schery and Petschek 1983;Wilson et al 1987). Falta et al (1989) found that (3) was in close agreement with numerically simulated gas velocities within porous media partially saturated by a volatile organic liquid. The maximum vertical velocity may not be realized elsewhere because of contaminant diffusion, constraining boundaries and forced advection.…”
Section: Transport Processesmentioning
confidence: 88%
See 1 more Smart Citation
“…This relationship was derived by a number of researchers using related approaches (Bear 1972;Turner 1973;Cheng and Minkowycz 1977;Schery and Petschek 1983;Wilson et al 1987). Falta et al (1989) found that (3) was in close agreement with numerically simulated gas velocities within porous media partially saturated by a volatile organic liquid. The maximum vertical velocity may not be realized elsewhere because of contaminant diffusion, constraining boundaries and forced advection.…”
Section: Transport Processesmentioning
confidence: 88%
“…A number of these models have simulated forced advection of dilute gases in soils, including Mohsen et al (1980) and Metcalfe and Farquhar (1987), who address methane release from landfills; Loureiro et al (1990), who model radon transport into the basement of buildings, and a number of models related to the transport of volatile organic solvents in unsaturated soil (Abriola and Pinder 1985;Baehr and Corapcioglu 1987;Gierke et al 1990). With the recognition that volatile organic liquids become trapped in the subsurface following their release, gas transport models have included the effects of volatilization and buoyancy-induced advection (Sleep and Sykes 1989;Falta et al 1989;Mendoza and Frind 1990;Mendoza and McAlary 1990). These models differ in their representation of the source term, and in the two-dimensional geometry and boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the application of the Stefan-Maxwell equations may be necessary for modelling gas phase diffusion (Baehr and Bruell, 1990;Van de Steene and Verplancke, 2006). Although some studies indicate that density-driven advection can play a role (Falta et al, 1989), this process was neglected. Gas phase diffusion also largely dominates over aqueous-phase diffusion (Schwarzenbach et al, 2003), and therefore the latter is neglected.…”
Section: Process Representation In the Modelmentioning
confidence: 99%
“…3,6−9 Chlorinated ethenes are transported away from the NAPL source by gaseous diffusion and may induce groundwater contamination even if the NAPL has not reached the water table. 10 Mass transport between unsaturated and saturated zones and inside the unsaturated zone thus plays an important role in controlling the fate of these contaminants. 11 Stable isotope analysis is increasingly used to investigate the behavior of organic or inorganic contaminants in the subsurface.…”
Section: ■ Introductionmentioning
confidence: 99%